Patient Satisfaction With Nursing Care In Ministry Of Health Hospitals In Saudi Arabia (The Review of Diabetic Studies, 2024)
Introduction: Patient satisfaction is a significant indicator of quality and effective outcomes for the health care delivery system, especially in the area of nursing and the quality of nursing care provided. The MOH controls and manages the majority of the public hospitals in Saudi Arabia; therefore, nursing care is a crucial component of the overall experience for the most patients. To implement the Vision 2030 program's health care reform plan, it is essential to comprehend the current levels of patient satisfaction among the MOH hospitals.Research Objective: The primary purpose of the present systematic review is to assess patients' experience with Nursing Care at the Ministry of Health (MOH) Hospitals in Saudi Arabia; additionally, this study will identify how these experiences are affected by various factors such as Communication, Empathy, Responsiveness, Cultural Sensitivity, and Professional Competence.Research Methods: A systematic review was performed according to PRISMA guidelines. A comprehensive search of the electronic databases (PubMed, Scopus, Web of Science, and Google Scholar) was conducted for empirical articles from 2015 to 2025. The keywords employed were "patient satisfaction," "nursing care," "Saudi Arabia," and "Ministry of Health hospitals." The articles chosen for inclusion were based on empirical studies and focused on measuring patient satisfaction with nursing care provided in the MOH Hospitals.Conclusion: According to the findings of this systematic review, patients in MOH Hospitals express moderate to high levels of satisfaction with nursing care; communication and level of empathy, as well as cultural sensitivity and the reception of care, are the strongest predictors of a positive patient experience. However, systemic issues such as staffing shortages, increased workloads and variations across regions are likely to negatively impact patient satisfaction with nursing care.